Presence of DDT metabolites in water, sediment and fish muscle tissue from Lake Prespa, Republic of Macedonia - Veljanoska-Sarafiloska, Elizabeta M; Jordanoski, Momčula; Stafilov, Trajče (My University, 2013)
Organochlorine pesticides were determined in water and sediment samples collected from the littoral zone of Lake Prespa, as well as from its three main tributaries (the rivers Golema, Brajcinska and Kranska), during the period 2004 to 2006. In addition, muscle tissue samples of barbus fish (Barbus prespensis Karaman, 1928) collected from the littoral zone of Lake Prespa were also analysed. The obtained results give an overview of the contamination levels of these problematic compounds at their potential sources in the river mouths, in the potentially affected, species-rich littoral section of the lake and in the muscle tissue of one selected fish species, collected near the rivers' deltas. Special attention was paid to the presence of some DDT metabolites (1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (p,p'-DDE); (1,1-dichloro-2,2-bis(p-chlorophenyl)ethane (p,p'-DDD) and 1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane (p,p'-DDT). The extraction of pesticides from water samples was done by liquid-liquid partition in dichloromethane. For the sediment and fish tissue we used solid-liquid extraction. The extracted residues were analyzed on a gas chromatograph equipped with an electron capture detector (GC-ECD). The results of the respective studies indicated the presence of DDT metabolic forms in the samples of the three analysed matrixes. The highest levels of presence for these pollutants were found in the muscle tissue of the fish samples. The total DDTs content in the analysed muscle tissue samples range from 11.67 to 13.58 μg kg⁻¹ of fresh tissue. The average total DDTs content for the sediment samples were within the range of 2.32 to 4.17 μg kg⁻¹ of dry sediment. Higher DDT metabolites content were found in the sediments collected from the rivers than in the samples from the littoral zone. The lowest average total concentrations of DDTs, on the other hand, were recorded in the water samples and ranged between 0.036 and 0.057 μg L⁻¹. The obtained results indicated that the dominant metabolic form in the samples of the three investigated matrixes (water, sediment and fish tissue) from Lake Prespa was p,p'-DDE. There was a very good linear correlation in this study between the content of DDT's (total DDT metabolites) detected and the percentage of total organic material in the sediment. The detected concentrations are clearly below the toxicity thresholds; consequently, severe effects on the endemic species of Lake Prespa are not very likely.